Effect of Deposition Rate on Morphology of Zinc Phthalocyanine Layer (ZnPc) on Polystyrene Surface / QCM with Vacuum Evaporation Process - Fadli Robiandi; Lalu A Didik; Eka Rahmawati; Susi Rahayu; Masruroh Masruroh; Setyawan P. Sakti; Djoko H Santjojo (Natural B, Journal of Health and Environmental Sciences, 2014)
Deposition of zinc phthalocyanine (ZnPc) layer on top polistiren surface by vacuum evaporation method has been investigated. PS layer was coated on QCM surface by spin coater and ZnPc layer was deposited on its surface by vacuum evaporator with three variation of deposition rate, i.e 1.39 ´ 10-4, 8.08 ´ 10-2 dan 7,41 ´ 10-1 μm/s. The morphology and surface roughness of ZnPc layer was observed by scanning electron microscope (SEM) and non-contact topography measurement system TMS-1200 TopMap. SEM image of ZnPc layer with deposition rate of 1.39 ´ 10-4, 8.08 ´ 10-2 and 7.41 ´ 10-1 μm/s shows porous and fibre like structure. The size of pores and fibre structures of ZnPc layer that produced by deposition rates of 1.39 x10-4 and 8.08 x10-2 μm/s is smaller than size of pores and fibre that produced by 7.41 ´ 10-1 μm/s. Moreover, increasing the deposition rate result a lot of ZnPc molecules make a bonding as fibrous result in the volume of fibrous increasing. Moreover, the increasing fibre size result pores volume increase. Therefore deposition rate can affect surface roughness, and roughness value is proportional to morphology of ZnPc layer. Based on result of TMS-1200 TopMap, the highest roughness level is 1310 nm, it’s found on the ZnPc layer that produced by deposition rate of 7,41 ´ 10-1 μm/s.